Resveratrol inhibits TGF-β1-induced fibrotic effects in human pterygium fibroblasts - Jianwu Fan; Shuang Wei; Xiaoyan Zhang; Li Chen; Xin Zhang; Yaping Jiang; Minjie Sheng; Yihui Chen (Komiyama Printing Co. Ltd, 2023)
Background: Resveratrol is a polyphenolic phytoalexin which has the properties of anti-oxidant, anti-inflammatory and anti-fibrotic effects. The aim of this study was to investigate the anti-fibrotic effects of resveratrol in primary human pterygium fibroblasts (HPFs) and elucidate the underlying mechanisms. Method: Profibrotic activation was induced by transforming growth factor-beta1 (TGF-β1). The expression of profibrotic markers, including type 1 collagen (COL1), α-smooth muscle actin (α-SMA), and fibronectin, were detected by western blot and quantitative real-time-PCR after treatment with various concentrations of resveratrol in HPFs to investigate the anti-fibrotic effects. Relative signaling pathways downstream of TGF-β1 were detected by Western blot to assess the underlying mechanism. Cell viability and apoptosis were assessed using CCK-8 assay and flow cytometry to evaluate proliferation and drug-induced cytotoxicity. Cell migration and contractile phenotype were detected through wound healing assay and collagen gel contraction assay. Results: The expression of α-SMA, FN and COL1 induced by TGF-β1 were suppressed by treatment with resveratrol in dose-dependent manner. The Smad3, mitogen-activated protein kinase (p38 MAPK) and phosphatidylinositol-3-kinase (PI3K) / protein kinase B (AKT) pathways were activated by TGF-β1, while resveratrol attenuated those pathways. Resveratrol also inhibited cellular proliferation, migration and contractile phenotype, and induced apoptosis in HPFs. Conclusions: Resveratrol inhibit TGF-β1-induced myofibroblast activation and extra cellular matrix synthesis in HPFs, at least partly, by regulating the TGF-β/Smad3, p38 MAPK and PI3K/AKT pathways.